2016
DOI: 10.1021/acs.est.5b04369
|View full text |Cite
|
Sign up to set email alerts
|

Cable Bacteria Control Iron–Phosphorus Dynamics in Sediments of a Coastal Hypoxic Basin

Abstract: Phosphorus is an essential nutrient for life. The release of phosphorus from sediments is critical in sustaining phytoplankton growth in many aquatic systems and is pivotal to eutrophication and the development of bottom water hypoxia. Conventionally, sediment phosphorus release is thought to be controlled by changes in iron oxide reduction driven by variations in external environmental factors, such as organic matter input and bottom water oxygen. Here, we show that internal shifts in microbial communities, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
141
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 35 publications
6
141
3
1
Order By: Relevance
“…This has been attributed to binding of P to Fe-(oxyhydr)oxides, which is supported by the presence of a large stock of Fe-bound P in the surface sediment (Sulu-Gambari et al 2016a). In this latter study, however, the stock of Fe-bound P was determined with an operational SEDEX extraction (Ruttenberg 1992) that can also extract vivianite (Dijkstra et al 2014;Dijkstra et al 2016;Egger et al 2015).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…This has been attributed to binding of P to Fe-(oxyhydr)oxides, which is supported by the presence of a large stock of Fe-bound P in the surface sediment (Sulu-Gambari et al 2016a). In this latter study, however, the stock of Fe-bound P was determined with an operational SEDEX extraction (Ruttenberg 1992) that can also extract vivianite (Dijkstra et al 2014;Dijkstra et al 2016;Egger et al 2015).…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, in a recent study of P cycling at a site in a seasonally hypoxic coastal marine basin (Lake Grevelingen, the Netherlands), Sulu-Gambari et al (2016a) demonstrated a lack of authigenic Ca-P formation at a site where polyphosphate-bearing Beggiatoaceae were abundant in autumn. In the latter setting, cable bacteria, a g r o u p o f s u l p h u r -o x i d i s i n g b a c t e r i a f r o m t h e Desulfobulbaceae family (Burdorf et al 2016;Nielsen et al 2010;Pfeffer et al 2012;Risgaard-Petersen et al 2012;Trojan et al 2016) that can also form polyphosphates in their cells were active in spring (Sulu-Gambari et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations